Analisis Penataan Perpustakaan untuk Meningkatkan Minat Baca di Sekolah Negeri 1 Demulih - Ni Komang Juni Rahayu (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to analyse the arrangement of the library to increase reading interest in State School 1 Demulih. The arrangement of the library in SD N 1 Demulih has not been fully implemented based on the flow of the library layout to facilitate and process the work done by the library staff, the library layout can attract students' interest in reading. This study uses a descriptive research method with a qualitative method. The data collection techniques used in this study are observation sheets and interview list sheets conducted at SD N 1 Demulih. The results of this study is the Library at SD N 1 Demulih have carried out several strategies for physical and non-physical arrangement of the library. The physical arrangement strategy that has been carried out is the location of the Library that is accessible to students, bright lighting and available air ventilation as well as providing facilities and infrastructure such as chairs and tables in good condition that can be used by students when reading the library collection. Providing these strategies is very important for readers so that students who read in the library feel comfortable and make them feel at home so that the students want to come back again to read.